2008
DOI: 10.1002/elps.200700732
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of rice glutelin polypeptides in wild species assessed by the higher‐temperature sodium dodecyl sulfate‐polyacrylamide gel electrophoresis and subunit‐specific antibodies

Abstract: In efforts to find genetic resources with high nutritional value of rice seed, we assessed the diversity of the major storage protein glutelin in 13 wild and 2 cultivated rice species by a unique SDS-PAGE method and subunit-specific antibodies. Maximum separation of microheterogeneous glutelin alpha-polypeptides, which is a prerequisite for the diversity evaluation, could be attained by SDS-PAGE performed at higher temperature (45 degrees C) than the generally employed temperatures (4-25 degrees C). Seven anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 43 publications
(50 reference statements)
2
23
0
Order By: Relevance
“…Electrophoresis in the first dimension (NEPHGE) was performed at 200 V for 15 min, 300 V for 15 min, 400 V for 15 min, 500 V for 15 min, and 750 V for 5 h. Electrophoresis in second dimension was carried out by higher temperature SDS-PAGE method according to Khan et al (2008a) at constant voltage of 200 V for 80 min at 45 °C. The immunoblotting was performed according to the method mentioned in our previous report (Khan et al, 2008a). Briefly, the proteins resolved by SDS-PAGE and 2D-PAGE were electrophoretically transferred to nitrocellulose membrane.…”
Section: Sds-page 2d-page and Western Blot Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrophoresis in the first dimension (NEPHGE) was performed at 200 V for 15 min, 300 V for 15 min, 400 V for 15 min, 500 V for 15 min, and 750 V for 5 h. Electrophoresis in second dimension was carried out by higher temperature SDS-PAGE method according to Khan et al (2008a) at constant voltage of 200 V for 80 min at 45 °C. The immunoblotting was performed according to the method mentioned in our previous report (Khan et al, 2008a). Briefly, the proteins resolved by SDS-PAGE and 2D-PAGE were electrophoretically transferred to nitrocellulose membrane.…”
Section: Sds-page 2d-page and Western Blot Analysesmentioning
confidence: 99%
“…The sections on a slide glass were treated with acetone, PBS, and blocking buffer followed by primary and secondary antibodies. The primary antibodies were 1,000-fold diluted anti-glutelin A1(No.2) antibody of mouse (Khan et al, 2008a) and 2000-fold diluted anti-alpha globulin antibody (prepared against peptide sequence LTGRERFQPMFRRPGALG in rabbit). The secondary antibodies were 500-fold diluted anti-mouse IgG conjugated FITC (green) and 2000-fold diluted anti-rabbit IgG conjugated Cy3 (red).…”
Section: Microscopic and Confocal Laser Microscopic Examinations Of Rmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the quantification of each subunit (band) by conventional 1-D gel electrophoresis is difficult because of insufficient band separation. Although an SDS-PAGE method at a higher temperature has been devised to maximize the separation [5], the quantification using this method requires a specific antibody reaction. The insufficient separation of the glutelin band is largely due to the microheterogeneity of the glutelin subunits.…”
Section: Quantification Of Glutelin Subunitsmentioning
confidence: 99%
“…Previously, we characterized the major subunits of glutelin and demonstrated that all GluA and GluB4 subunits polymerize because of a specific cysteine (Cys) residue [2]. We have also raised subunitspecific antibodies to determine the subunit diversity in African rice and 18 wild species [5]. Although promising wild species were identified, large-scale screening, which is inefficient using gel electrophoresis, might be necessary for the further identification of superior germplasms.…”
Section: Introductionmentioning
confidence: 98%